Keragaan Koperasi Dan Potensi Pengembangan Koperasi Simpan Pinjam Keluarga Besar Al-Muttaqien Sukajadi - Ellin Sinta Dewi; Dini Evita Sari; Frita Azalea Zahra (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2022)
Cooperatives create jobs and increase income so that they are expected to be able to realize a safe and peaceful, just and democratic, and prosperous Indonesia. This condition will be difficult to realize if people still live in poverty and high unemployment rates, as well as economic inequality and inequality in the control of productive resources in the community. Cooperatives will not be attractive to members, prospective members and other people who want to become members, because they only feel they have excess capital. The purpose of this research is to provide a real picture for the practitioner to know, study, analyze, and provide a real picture to students regarding the environmental conditions of the world of work. This research uses case study research method. From this study, it was found that the financial statements in 2020 were considered to be lacking because the percentage ratio was still below the cooperative standard. From the aspect of the financial statements, it was complete and clear with the recording of each transaction and an explanation of each nominal entry and exit. Based on the SWOT analysis Koperasi Simpan Pinjam Keluarga Besar Al-Muttaqien Sukajadi has strengths and opportunities to deal with existing weaknesses and threats.